Prognostic Power of Cerebroplacental Ratio for Adverse Fetal Outcomes in Women with High-Risk Pregnancies - Batool, Saima; Bhatti, Rabia; Sahar, Amara (Biological and Clinical Sciences Research Journal, 2025)
High-risk pregnancies are associated with increased risk of adverse fetal outcomes, including perinatal mortality and morbidity. The cerebroplacental ratio (CPR), derived from Doppler assessment of fetal umbilical artery (UA) and middle cerebral artery (MCA) pulsatility indices (PIs), has been proposed as a non-invasive predictor of such outcomes. However, its predictive accuracy remains variable in clinical practice. Objective: To evaluate the predictive ability of cerebroplacental ratio for adverse fetal outcomes in women with high-risk pregnancies. Methods: This retrospective study was conducted in the Department of Obstetrics and Gynaecology at Nishtar Hospital, Multan, from February 2024 to February 2025. A total of 100 pregnant women with singleton pregnancies between 32 and 40+6 weeks of gestation were included. All participants underwent Doppler ultrasonography to assess UA-PI, MCA-PI and to calculate the CPR. The primary outcome was the incidence of perinatal adverse outcomes such as stillbirth, neonatal death, low 5-minute Apgar score, seizures, and grade II or III neonatal encephalopathy. Secondary outcomes included the incidence of small-for-gestational-age (SGA) fetuses among live births, SGA fetuses with morbidity, and morbidity in appropriate-for-gestational-age (AGA) fetuses. Data were analyzed using receiver operating characteristic (ROC) curves, and area under the curve (AUC) values were compared. Results: UA-PI, MCA-PI, and CPR were all poor predictors of perinatal mortality, with AUCs of 0.61, 0.55, and 0.58, respectively, showing no significant difference in accuracy. For the prediction of SGA fetuses, CPR demonstrated a significantly higher z-score (0.75) compared to MCA-PI (0.71) and UA-PI (0.72). CPR and MCA-PI both had moderate predictive value for morbidity in AGA fetuses (AUC: 0.65), outperforming UA-PI (AUC: 0.58). For morbidity prediction in SGA fetuses, CPR (AUC: 0.76) and MCA-PI (AUC: 0.75) exhibited similar prognostic accuracy, both superior to UA-PI (AUC: 0.65). Conclusion: While Doppler indices including CPR, MCA-PI, and UA-PI demonstrated limited utility in predicting perinatal mortality, CPR and MCA-PI were relatively better predictors of neonatal morbidity, particularly in small-for-gestational-age fetuses. These findings support the clinical value of CPR and MCA-PI in fetal surveillance during high-risk pregnancies.